Evaluation on Enterprises’ Service Flexible Capability Based on Reverse Supply Chain - Xu Chang; Li Jiujin; Yang Donghong (International Journal of Supply Chain Management, 2014)
Due to the characteristics such as complexity and uncertainty etc., there are many difficulties during the performing of reverse supply chain. In order to effectively play the role of reverse supply chain, obtain lasting economic, ecological and social benefits, this paper introduces the concept of service flexible capability, and contributes an evaluation index system of it for enterprises. Due to fuzziness of the indicators, combined with AHP, this paper takes a real enterprise for example, evaluates the enterprises service flexible capability by fuzzy comprehensive evaluation method. According to the evaluation process and evaluation results, the enterprises service flexible capability can be mastered better.